The Influence of Financial Technology, Financial Inclusion and Credit Accessibility on the Sustainability of MSMEs (Case Study on MSMEs in Cirebon Regency) - Pertiwi, Widjia; Indriyani, Rinni; Sari , Fitriya (Journal of Economics and Business UBS, 2025)
This study aims to analyze the influence of financial technology, financial inclusion, and credit accessibility on the sustainability of MSMEs in Cirebon Regency, both partially and simultaneously. The study used a quantitative approach with a sample of 100 respondents determined through probability random sampling technique through a questionnaire based on the Likert scale and analyzed with SPSS 26. The results of the study show that financial technology has a positive and significant effect on the sustainability of MSMEs, shown using digital services such as e-wallets and financial recording applications that increase operational efficiency. Financial inclusion also has a positive and significant effect, where bank account access and digital payment services are the dominant factors even though the understanding of financial products is still low. On the other hand, credit accessibility has a negative and insignificant effect, reflecting the existence of procedural barriers and the lack of utilization of formal credit facilities. Simultaneously, the three variables have a significant effect on the sustainability of MSMEs with a contribution of 42.8%. This study emphasizes the importance of digitizing financial services and expanding access to formal finance in encouraging the sustainability of MSMEs and the support of local governments and financial institutions need to improve financial education, expand affordable fintech services, and simplify credit procedures so that MSMEs can survive and develop sustainably.